2019
DOI: 10.1016/j.appet.2019.104371
|View full text |Cite
|
Sign up to set email alerts
|

Maternal feeding practices and children's food intake during an ad libitum buffet meal: Results from the GUSTO cohort

Abstract: Parents' feeding practices have been shown to be associated with children's food intake and weight status, but little is known about feeding practices in Asian countries. This study used behavioral observation to explore the feeding practices of 201 mothers of 4.5 year-old children in Singapore during an ad libitum buffet lunch. Feeding practices were coded from videos, focusing on behaviors used to prompt the child to eat more food (autonomy-supportive and coercivecontrolling prompts to eat, suggesting items … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 53 publications
0
28
0
Order By: Relevance
“…Mothers of young children in Singapore also tend to show a high level of involvement in their children's eating behaviors (Fries et al, 2019). Past studies have found that controlling parenting practices related to food and maternal feeding restriction is associated with persistent problematic eating (Ellis, Galloway, Webb, Martz, & Farrow, 2016; Fernandez et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Mothers of young children in Singapore also tend to show a high level of involvement in their children's eating behaviors (Fries et al, 2019). Past studies have found that controlling parenting practices related to food and maternal feeding restriction is associated with persistent problematic eating (Ellis, Galloway, Webb, Martz, & Farrow, 2016; Fernandez et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Parent‐reports of child diet are vulnerable to recall errors and bias, 33 and are known to overestimate child consumption, particularly at preschool age 34 . Further, many of the studies utilizing behavioral tests of appetite have taken place at home or in laboratory settings 9,35,36 . The latter (laboratory meal tests) allow for controlled manipulations of different food options and enable objective, standardized comparisons of objectively measured intake, but these artificial settings could also influence children's food consumption, especially when tests are administered on just one occasion.…”
Section: Introductionmentioning
confidence: 99%
“…Environmental factors influence a child's eating. Feeding practices, including parental interactions, influence what a child eats, a child's weight, diet, food acceptance, and eating behaviors (Blissett, 2011;Edelson et al, 2016;Fogel et al, 2018;Fries, Chan, et al, 2019;. Fogel et al (2018) found that children who eat faster and have high energy intake were prompted to eat during mealtime.…”
Section: How Do We Include Parental Involvement In the Development Of The Hut Method?mentioning
confidence: 99%
“…Within food texture specifically, texture preferences and the role of early eating experiences were previously explored using a HUT (Blossfeld, Collins, Kiely, & Delahunty, 2007). The application of observational methods in feeding studies has also been employed to better understand eating from an objective standpoint, using trained coders and a well-developed coding scheme (Fries, Chan, et al, 2019).…”
Section: What Type Of Test Should We Use?mentioning
confidence: 99%
See 1 more Smart Citation